PERLINDUNGAN HUKUM BAGI IRREGULAR MIGRANT WORKERS INDONESIA DI KAWASAN ASIA TENGGARA (DALAM PERSPEKTIF HUKUM HAM INTERNASIONAL) - Riri Anggriani (Universitas Airlangga, 2017)
The development of globalization that occurred has considerable impact for human life and for countries in Southeast Asia. One is the movement of people from one country to another, especially concerning the problem of economic migrants seeking employment or working in a country where they work especially irregular migrant workers. These irregular migrants are vulnerable to violations of their human rights. The issue is how the protection of the law is provided by the country of origin through Indonesian national law in countries that are the destination of Indonesian migrant workers in the Southeast Asian Region through the perspective of international human rights law. This research is legal research. The results of this study indicate that Indonesian migrant workers with the status of irregular migrant workers are workers who also have the same rights as other migrant workers or other citizens so that countries (especially countries in Southeast Asia) have an obligation to acknowledge and Protect them wherever they may be or under any circumstances they experience as contained in the provisions of international human rights law, especially in the Convention on the Protection of the Rights of All Migrant Workers and their Families (CMW), 1990.